1993
DOI: 10.1159/000119025
|View full text |Cite
|
Sign up to set email alerts
|

<sup>123</sup>I-IMP SPECT Brain Imaging in Epileptic Psychosis: A Study of Two Cases of Temporal Lobe Epilepsy with Schizophrenia-Like Syndrome

Abstract: To examine the relationship between functional abnormality of the brain and the development of epileptic psychosis, regional cerebral blood flow (rCBF) patterns with single photon emission computed tomography (SPECT) using N-isopropyl-(iodine-123)-p-Modoamphetamine (123I-IMP) were serially examined in interictal stages with and without the psychotic state in 2 medicated patients with temporal lobe epilepsy with schizophrenia-like syndrome. Both patients had epileptic EEG foci in the left temporal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…A relationship between TLE and psychosis is still discussed; however, some authors supposed that the apparent excess of TLE in patients with both epilepsy and psychosis is explained by the fact that TLE is the most common type of chronic epilepsy [44, 45]. Several studies postulated that psychosis affects in particular patients with left TLE [46,47,48,49,50]. In our sample, only 7 patients presented psychotic features (3% of the total sample, and 8% of the EPI-PSY group), making any conclusion in terms of lateralization difficult.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between TLE and psychosis is still discussed; however, some authors supposed that the apparent excess of TLE in patients with both epilepsy and psychosis is explained by the fact that TLE is the most common type of chronic epilepsy [44, 45]. Several studies postulated that psychosis affects in particular patients with left TLE [46,47,48,49,50]. In our sample, only 7 patients presented psychotic features (3% of the total sample, and 8% of the EPI-PSY group), making any conclusion in terms of lateralization difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Studies other than EEG provided some evidence that hyperfunction may be involved in the pathogenesis of psychosis. A single‐photon emission computed tomography (SPECT) study conducted by Jibiki et al (9) reported two cases of periictal psychosis showing hyperperfusion in the temporolimbic system during psychotic states. Another SPECT study of four patients with temporal lobe epilepsy demonstrated medial frontal hyperperfusion during psychosis (10).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot SPECT study was carried out to compare rCBF in patients with epilepsy with and without a schizophrenia-like psychosis: SLPE patients exhibited a significant reduction in the normalized rCBF index in the left hemisphere that was confined to the mediotemporal region Jibiki et al (102), studying the rCBF patterns with SPECT, suggested that temporolimbic dysfunction, particularly hyperfunction in the temporolimbic system in the dominant left hemisphere, appears to arise at the time of the psychotic state in epileptic psychosis (102). consistent with the theory that a state of psychosis arises when episodic dopamine excess is superimposed on a trait of basic dopamine deficiency in the striatum.…”
Section: Neuroimaging In Epileptic Psychosesmentioning
confidence: 99%